Open patellar tendon avulsion from tibial tuberosity after ACL reconstruction successfully treated with suture anchors - Regis, Dario; Sandri, Andrea; Bizzotto, Nicola; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2019)
Patellar tendon rupture after anterior cruciate ligament (ACL) reconstruction is a rare complication which usually occurs in the early postoperative period during rehabilitation. The management of open avulsions from tibial tuberosity has not been clearly defined yet. We describe a previously unreported case of traumatic and open patellar tendon avulsion from tibial tuberosity one year following ACL reconstruction in an elite football player which was successfully treated with suture anchors.